Blood-Brain Barrier Dysfunction in Small Vessel Disease Related Intracerebral Hemorrhage - Freeze, Whitney M.; Jacobs, Heidi I. L.; Schreuder, Floris H. B. M.; van Oostenbrugge, Robert J.; Backes, Walter H.; Verhey, Frans R.; Klijn, Catharina J. M. (Frontiers in Neurology, 2018)
Background and Purpose: Hypertensive vasculopathy and cerebral amyloid angiopathy are the two most common forms of cerebral small vessel disease. Both forms are associated with the development of primary intracerebral hemorrhage, but the pathophysiological mechanisms underlying spontaneous vessel rupture remain unknown. This work constitutes a systematic review on blood-brain barrier dysfunction in the etiology of spontaneous intracerebral hemorrhage due to cerebral small vessel disease. Methods: We searched Medline (1946–2018) and Embase (1974–2018) for animal and human studies reporting on blood-brain barrier dysfunction associated with intracerebral hemorrhage or cerebral microbleeds. Results: Of 26 eligible studies, 10 were animal studies and 16 were in humans. The authors found indications for blood-brain barrier dysfunction in all four animal studies addressing hypertensive vasculopathy-related intracerebral hemorrhage (n = 32 hypertensive animals included in all four studies combined), and in four of six studies on cerebral amyloid angiopathy-related intracerebral hemorrhage (n = 47). Of the studies in humans, five of six studies in patients with cerebral amyloid angiopathy-related intracerebral hemorrhage (n = 117) and seven out of nine studies examining intracerebral hemorrhage with mixed or unspecified underlying etiology (n = 489) found indications for blood-brain barrier dysfunction. One post-mortem study in hypertensive vasculopathy-related intracerebral hemorrhage (n = 82) found no evidence for blood-brain barrier abnormalities. Conclusions: Signs of blood-brain barrier dysfunction were found in 20 out of 26 studies. Blood-brain barrier integrity deserves further investigation with a view to identification of potential treatment targets for spontaneous intracerebral hemorrhage.